2005
DOI: 10.1111/j.1468-3083.2005.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired aquagenic papulotranslucent acrokeratoderma

Abstract: We report the case of a healthy 16-year-old male with progressively increasing brown macules arranged in a zosteriform pattern on the left abdomen and back. The lesion appeared at the age of 15 and has been enlarged since then. He had no history of any preceding eruption or injury to the area. He had no evidence of internal diseases. His family had no history of skin abnormalities. He was not taking any medications. Physical examination revealed linear, cribriform, brown macular pigmentation arranged in a zost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…The latency of lesions after water contact has spanned 2–10 min, 5 as in our patients. According to the previous publications (Table 1), 1–23 AA has a predilection for adolescents and females, 21 and involvement of the palms and fingers. In addition to our patient 1, there are only three other cases in the literature with sole involvement 3,8,10 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The latency of lesions after water contact has spanned 2–10 min, 5 as in our patients. According to the previous publications (Table 1), 1–23 AA has a predilection for adolescents and females, 21 and involvement of the palms and fingers. In addition to our patient 1, there are only three other cases in the literature with sole involvement 3,8,10 .…”
Section: Discussionmentioning
confidence: 92%
“…The transient reactive type was first reported by English and McCollough 1 in 1996, in two sisters, and was characterized by translucent to whitish papules involving the palms, associated with burning sensation after 3–5 min of water exposure; lesions resolved soon after withdrawal of water. The disorder was termed “transient reactive papulotranslucent acrokeratoderma.” Since then, more than 30 cases have been described 1–23 (Table 1) under different names, depending on the accompanying features, including “aquagenic palmoplantar keratoderma”, 3 “aquagenic syringeal acrokeratoderma”, 5 “aquagenic keratoderma”, 7 “aquagenic wrinkling of the palms”, 11 and “aquagenic acrokeratoderma” (AA) 12 . The “hand‐in‐the‐bucket” sign, when patients submerge their hands in water to demonstrate the lesions, is a diagnostic clue.…”
Section: Introductionmentioning
confidence: 99%
“…TAPH usually develops in puberty or in the early 20s (average 20.9 years, age range 8–35), and initial reports suggested that predominantly females are affected. More recently however, several reports claiming the first description in males were almost simultaneously published [9, 15, 16]. The average duration of TAPH before consulting a physician was 14.8 months, with a range of 3 weeks to 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…A search of the English literature using all proposed terms of TAPH identified 24 cases in the dermatological literature which are summarized in table 1[1,2,3, 5,8,9,10,11,12,13,14,15,16,17,18,19]. However, not included are 12 additional cases of TAPH associated with CF which were published in the 1970s by paediatricians, but lack detailed clinical information [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Falcón et al (1 case) 21 Pastor et al (3 cases) 22 Pardo et al (1 case) 23 Badazzi et al (1 case) 12 Sais et al (1 case) 24 Conde-Salazar (2 cases) 25 Luo et al (2 cases) 26 27 Polat et al (2 cases) 28 Yalcin et al (1 case) 29 Adişen et al (1 case) 30 Itin et al (1 case) 8 Suchak et al (1 case: the same case improved with aluminium hydroxide) 16 Luo et al (1 case: the same case improved with formalin 3%) 26 …”
Section: Case Reportmentioning
confidence: 99%